An empirically grounded framework to guide blogging for digital scholarship - Shailey Minocha; Tania Heap (Association for Learning Technology, 2012)
This research project investigated how openness and sharing of knowledge are manifested through scholarly blogging. We aimed to identify the academics’ and researchers’ motivations for starting a blog; the contribution of blogging to their personal and professional development; and any challenges. Twenty-six participants were recruited. A pre-interview questionnaire was first emailed to the participants to collect background information. An initial unstructured interview was conducted by email, followed by a synchronous semi-structured interview. Textual and visual extracts of blog content were also collected. The datasets were analysed using different techniques. The findings revealed varied reasons for blogging. Some academics/researchers began a blog for its accessibility to self and others. Blogging aided the academics’ and researchers’ personal and professional development in several ways. Bloggers can quickly reach a wider audience compared to other forms of academic publishing. Among the challenges, there were concerns over validity of online content. Based on previous scholarship models and on our findings, we have derived an empirically grounded framework of blog use in academia and research. The framework describes how characteristics of digital scholarship such as openness and sharing are manifested through blogging. The framework can be used to guide academics and researchers who are interested in taking up blogging as a scholarly practice.